2016
DOI: 10.1123/jpah.2016-0297
|View full text |Cite
|
Sign up to set email alerts
|

Results From Finland’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background: Finland's 2016 Report Card on Physical Activity for Children and Youth gathers and translates research results and assesses the status and promotion of physical activity (PA) among Finnish children and youth less than 18 years of age. This article summarizes the results and provides grades for 9 indicators. Methods: The working group evaluated the evidence and assigned grades of A (highest, 81% to 100%), B, C, D, or F (lowest, 0% to 20%) for 9 PA indicators using the Active Healthy Kids Canada Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
(5 reference statements)
1
18
0
Order By: Relevance
“…Active Transportation grades showed a wide distribution with the Netherlands reporting an A, 44 Zimbabwe an A-, 61 7 countries a B, 19 countries a C, 5 countries a D, 2 countries (United Arab Emirates, 56 United States 57 ) an F, and 3 countries an INC. While active transportation may be a necessity for some children in countries such as Zimbabwe, 61 Nigeria, 46 and Kenya, 40 in other countries with high grades it represents a choice that may be driven more by supportive policies and/or traditional cultural norms (eg, Denmark, 31 Finland, 34 the Netherlands 44 ). Multicountry studies have shown similar proportions of active transportation involvement in significantly differing contexts.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
“…Active Transportation grades showed a wide distribution with the Netherlands reporting an A, 44 Zimbabwe an A-, 61 7 countries a B, 19 countries a C, 5 countries a D, 2 countries (United Arab Emirates, 56 United States 57 ) an F, and 3 countries an INC. While active transportation may be a necessity for some children in countries such as Zimbabwe, 61 Nigeria, 46 and Kenya, 40 in other countries with high grades it represents a choice that may be driven more by supportive policies and/or traditional cultural norms (eg, Denmark, 31 Finland, 34 the Netherlands 44 ). Multicountry studies have shown similar proportions of active transportation involvement in significantly differing contexts.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
“…Differences have been reported by gender, whereby more boys (23.4%) meet the PA recommendations than girls (13.9%) [8]. There is also a decline in PA levels as age increases from 49% in primary school to 18% in lower secondary school that meet the PA recommendations [10]. In addition, despite Finnish adolescents experience the least amount of inequality to other countries in Europe [11], there is an association between higher financial wealth status and more days of reported PA [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, half (51%) of young adolescents aged between 11 and 15 years old reported to actively take part in sport clubs [11]. However, the rate of sports club membership reduced from 58% in 11 years olds to 35% in 15 year olds [12]. The organizational structure in sports clubs can be divided into three levels-macro, meso and micro.…”
Section: Introductionmentioning
confidence: 99%